Perceived creativity in insight problems by secondary school students: Effects of problem and solver’s variables - Yousfi, Hanane (2024)
Objective: The study analyzes secondary school students’ perceptions of creativity in insight problems. Methodology. An empirical study was conducted with a total of 127 Spanish students from 8th grade and 11th grade. The students evaluated the creativity involved in the problems before and after attempting to solve them. These evaluations were related to grade, gender, surface, and structural aspects of the problems. Everyday life and science contexts were considered as problem surfaces. The structural aspects of the problems were associated with the specific strategy needed to solve them, such as chunk decomposition and constraint relaxation, the assistance provided by the problem statement to initiate the resolution process, and the possibility of metacognitive control over the quality of the solution. Individual booklets with counterbalanced statements were prepared to assess perceived creativity and to solve the problems. Results. Contrary to expectations, students were able to mentally represent the structural aspects of the problems during reading, and before solving them. The problem surface did not significantly affect the initial perception of creativity. After solving the problems, the average changes in perceived creativity were small. Conclusions. The results encourage teachers to use insight problems to promote creativity in secondary school classrooms.